2013 35th International Conference on Software Engineering (ICSE) 2013
DOI: 10.1109/icse.2013.6606648
|View full text |Cite
|
Sign up to set email alerts
|

A study of enabling factors for rapid fielding combined practices to balance speed and stability

Abstract: Abstract-Agile projects are showing greater promise in rapid fielding as compared to waterfall projects. However, there is a lack of clarity regarding what really constitutes and contributes to success. We interviewed project teams with incremental development lifecycles, from five government and commercial organizations, to gain a better understanding of success and failure factors for rapid fielding on their projects. A key area we explored involves how Agile projects deal with the pressure to rapidly delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…Architecture design is "up-front" work, which appears to be contradictory to agility. Although we believe, and much research has shown, that architectural principles and agile practices are actually well aligned [6][8] [10], this position has not always been universally accepted.…”
Section: Architecture-centric Agile Analytics Developmentmentioning
confidence: 98%
“…Architecture design is "up-front" work, which appears to be contradictory to agility. Although we believe, and much research has shown, that architectural principles and agile practices are actually well aligned [6][8] [10], this position has not always been universally accepted.…”
Section: Architecture-centric Agile Analytics Developmentmentioning
confidence: 98%
“…Similarly, losing sight of the big picture is also on the list of the top six concerns with agile development (Begel and Nagappan 2007). Recently, Bellomo (Bellomo et al 2013) explored how agile projects deal with the pressure to rapidly deliver high-value capabilities and found that incorporating refactoring with other development practices can be useful in being able to respond quickly to unanticipated stability problems.…”
Section: Backgrounds and Related Workmentioning
confidence: 99%
“…But mandating tight scheduling constraints, may put off or prevent major redesigns, thus also putting off or preventing the creation of a reliable, stable, product with the flexibility needed to respond to rapid market changes (Kataoka et al 2002;Bellomo et al 2013). All too often, when decision makers pursue quick responses to the market, needed refactoring is deferred, code quality is reduced, and the refactoring that is eventually needed becomes more difficult and costly (Elssamadisy and Schalliol 2002).…”
mentioning
confidence: 99%
“…Bellomo et al (2013) state that both industries and governments have been increasingly adopting agile-based incremental software development practices due to their ability to improve speed. Furthermore, lean development has been proposed as away to achieve substantial cost savings and quality improvements (Radnor and Walley, 2008).…”
Section: Introductionmentioning
confidence: 99%